Bibliometric Analysis: Development of Electronic Teaching Materials for Physics Laboratory Courses to Train Scientific Creativity of Prospective Physics Teachers - Muhammad, Nurlaela; Taib, Suryani; Misbah, Misbah; Zulfah, Raihanah (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2023)
The development of electronic teaching materials continues to be carried out, so that there are many articles that examine this matter. Comprehensive information regarding its development is carried out by reviewing electronic teaching materials research documents using bibliometric analysis. Data mining was carried out on May 1, 2023 by searching the Scopus database using the keywords